Identifikasi Produk Bahan Makanan yang Berbahan Dasar Alga : Mikroalga atau Makroalga pada Pasar Tradisional dan Modern yang ada di Kota Medan A - Kinanti, Aulia Andin; Nasution, Aziz Husein; Wardana, Balqis Putri; Handayani, Fitriya; Ulfa, Syarifah Widya (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2024)
ABSTRACT Research on the identification of food products made from algae (microalgae or macroalgae) at traditional and modern markets in the city of Medan was carried out on May 26 2023. This research was carried out at traditional and modern markets in the city of Medan. The purpose of this research is as information and also as an extension of our knowledge about food products made from algae in traditional and modern markets in the city of Medan. The analysis uses a qualitative descriptive method, by taking samples, then documenting them by taking pictures, then identifying them. Analysis using a qualitative descriptive method was carried out in a way, every time you find a food product made from algae, a picture will be taken as proof that the product uses algae-based ingredients. The results of this study are that there are several food products that are often consumed which are made from algae found in traditional and modern markets in the city of Medan, namely jelly, nutrijel, pudding, nori and also karagean. Keywords: Identification, algae, food products